Contextual safeguarding and child protection : rewriting the rules - Firmin, Carlene (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book offers a complete account of Contextual Safeguarding theory, policy and practice frameworks for the first time. It highlights the particular challenge of extra-familial routes through which young people experience significant harm, such as child sexual exploitation, criminal exploitation, serious youth violence, domestic abuse in teenage relationships, bullying, gang-association and radicalisation"--
OCLC-licensed vendor bibliographic record.
Keywords: Child welfare -- Great Britain; Child abuse -- Great Britain -- Prevention; SOCIAL SCIENCE / Social Work; SOCIAL SCIENCE / Volunteer Work; SOCIAL SCIENCE / Children's Studies